Research on the Construction of Practical Training Teaching System for Health Service and Management Major from the Perspective of Industry-Academia Integration - Xing, Jianhong (Education Insights, 2026)
In the context of the "Healthy China 2030" strategy and the in-depth advancement of vocational education industry-academia integration innovation, the health service and management major serves as the core carrier for cultivating specialized talents in the rapidly expanding big health industry. Consequently, the quality of its practical training directly determines the overall effectiveness of applied talent cultivation. Currently, significant challenges persist in this major's practical training teaching, including shallow collaboration between academic institutions and enterprises, loose integration of specific job requirements with academic courses, weak practical training resources, and incomplete evaluation mechanisms. These deficiencies ultimately lead to insufficient job competence among graduates, making it difficult to meet the high-quality development needs of the modern healthcare sector. Based on the core concept of industry-academia integration and combined with rigorous industry job competency standards, this paper constructs a comprehensive, integrated practical training teaching system. This framework is developed across five critical dimensions: teaching objectives, course content, training platforms, faculty building, and evaluation mechanisms. Furthermore, the study proposes strategic implementation paths, such as collaborative education, the seamless integration of jobs, courses, competitions, and certifications, alongside a robust guarantee system encompassing institutions, resources, and faculty members. Ultimately, this research aims to resolve the critical pain point of professional practical training teaching being disconnected from industry reality, thereby improving the adaptability of talent cultivation and providing a valuable reference for the ongoing teaching innovation within the health service and management major.